Analisis Sistem Perbandingan Pendidikan di Negara Amerika Serikat dengan Negara Indonesia - Yola Putri Julian; Mislaini Mislaini; Laras Yulia Sari (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
This study aims to see and find out how the comparative analysis of the education system in the United States and Indonesia. The focus of this study is to see the match of education in America with Indonesia. The method used in this study is a literature review and the internet. This article aims to analyze the comparison of the education system between the United States and Indonesia. In this study, a study was conducted on various important aspects of the education systems of both countries, including the curriculum, education structure, government policies, and the quality of human resources in the education sector. Using a comparative approach, this article identifies the advantages and disadvantages of each system, as well as their influence on the development of education and the quality of human resources. The results of the analysis show that although the United States has a more flexible education system with higher innovation, Indonesia still faces major challenges in terms of education equity and teaching quality. This article is expected to provide useful insights for education policy makers in both countries to improve the quality and effectiveness of the education system in the future.